Business Dispute Resolution through Alternative Dispute Resolution (ADR): A Civil Law Analysis of the Effectiveness of Non-Litigation Mechanisms - Ani Purwati; Dora Kusumastuti; Geofani Milthree Saragih; Ade Sathya Sanathana Ishwara; A. Rachmat Wirawan (JURNAL AKTA, 2026)
This study examines the resolution of business disputes through Alternative Dispute Resolution (ADR) mechanisms, analyzing their effectiveness from a civil law perspective. Amid the limitations of litigation in accommodating the practical needs of business actors, this research investigates several problems, namely the normative foundations of ADR within civil law-based business dispute resolution, the effectiveness of non-litigation mechanisms in resolving business disputes, and the challenges and limitations of ADR within civil law systems. A normative juridical method is employed, combining statutory and conceptual approaches to analyze civil law doctrines, ADR regulations, and relevant legal literature. The findings show that ADR is normatively grounded in the principles of party autonomy, freedom of contract, good faith, and legal certainty, positioning it as an integral component of civil law rather than a mere alternative to litigation. Non-litigation mechanisms prove effective in delivering time and cost efficiency, confidentiality, and the preservation of business relationships, although constrained by power imbalances, enforceability issues, and limited institutional capacity. This study concludes that strengthening ADR's normative framework and institutional integration is essential to enhance its effectiveness in civil law-based business dispute resolution.